Դարձյալ Դավիթ Բեկի ծագումնաբանության հարցի շուրջ - Այվազյան, Հովհաննես (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Биографические данные о лидере освободительных движений Сюника в XVIII веке Давиде Беке очень скудны, если не сказать, что вообще отсутствуют. Объединив анализ исследований разных авторов, отдельных свидетельств и рукописей, можно сделать вывод: 1. Давид Бек, скорее всего, из Сюника, уроженец Татева, что, по всей видимости, и стало причиной его избрания лидером освободительных движений Сюника. 2. Основываясь на подлинности имен генеалогических записей, приведенных в Урпелеанском свидетельстве, весьма вероятно, что отец Давида Бека, Аствацатур, действительно происходил из рода Мелика Парсадана, являлся сыном Мелика Бали I, братом Мелика Парсадана II (Саргис Бек) и Ильи, что в свое время было записанно Ервандом Лалаяном. The biographical information on David Bek, the leader of the liberation movement of Syunik of the 18th century, is scant or non-existent. The combined analysis of the research conducted by different authors, separute evidence and manuscripts, enables us to conclude: 1. David Bek was presumably from Syunik, born in Tatev. In all likelihood, this was the reason he became the leader of the liberation movement of Syunik. 2. Genealogy records from the Urpeleants Certificate indicate that most probably David Bek’s father – Astvatsatur, actually descended from the Melik Parsadan lineage, was the son of Melik Bali I, the brother of Melik Parsadan II (Sargis Bek) and Ilya. This evidence was previously registered by Yervand Lalayan. 3. Contrary to popular belief that David Bek was not married and did not have a family, the documents contain reliable information that he was married and had heirs.
Keywords: Հայոց պատմություն